Saratov life of brothers Boris and Gleb Gnedenko - Anikin, Valery Mikhailovich; Gnedenko, Dmitry B.; Fedorova, Marina A. (Известия Саратовского университета. Новая серия Серия: Физика, 2023)
Background and Objectives: The purpose of the paper is to reflect on the development of physical and mathematical education in Saratov in 1920–1930 using the biographies of the Gnedenko brothers, Gleb V. Gnedenko (1909–1943) and Boris V. Gnedenko (1912–1995). In April 1925, the Gnedenko family moved to Saratov motivated by the parents’ desire to give their children good education. In 1932, the older brother, Gleb Gnedenko, received a diploma from the Saratov Pedagogical Institute. The younger brother, Boris Gnedenko, entered the Physics and Technology Department of the Pedagogical Faculty of Saratov University in 1927, at the age of 15, and graduated in 1930, well ahead of the schedule. Over the years of learning, the talented Gnedenko brothers stood out for their dedication to knowledge and their desire to help their classmates. Gleb Gnedenko, after completing his postgraduate studies at the K. Liebkhnecht Pedagogical Institute in Moscow and working at the Tyumen Pedagogical Institute, returned to teaching in Saratov, where he had worked at the Saratov Pedagogical Institute and at the German Pedagogical Institute (Engels city). With the beginning of the Great War II, he was enlisted into the Soviet Army and died heroically in October 1943 while crossing the Dnieper River in Ukraine. In Saratov city, his name is listed on the obelisk in memory of the Pedagogical Institute’s lecturers who did not return from the war. Boris V. Gnedenko was an outstanding mathematician who worked in the field of probability theory and its applications. He is known for his achievements in the probability theory and mathematical statistics, the queuing theory, and the reliability theory. He was an expert in history,methodology and philosophy ofmathematics. His book “A Course in Probability Theory” has been a worldwide bestseller for decades. Boris V. Gnedenko stood at the origins of the creation of computer technology in the former Soviet Union. His total number of scientific, methodological, and popular publications is close to 1300. Materials and Methods: The article uses family archives, Boris V. Gnedenko’s memoirs, and his students’ recollections, as well as the archive materials on the history of the Saratov State University. Conclusion: The Gnedenko brothers were people of great spiritual generosity, modesty, and chivalrous quality. They were being easy to communicate with and at the same time firm and principled in defending their views and beliefs. The brothers’ personal life and professional activities reflect very well the character and history of the pedagogical, physical, and mathematical departments at the Saratov University and at the Saratov Pedagogical Institute in the 1920s-1930s.